The Ambivalence of Early Diagnosis - Returning Results in Current Alzheimer Research - Erdmann, Pia; Langanke, Martin (Current Alzheimer Research, 2018)
Objectives: Based on an analysis of the potential consequences of disclosing AD suspicions from respective research and using the research ethical principle of non-maleficence, the authors of this paper argue for the thesis that the benefits of early AD detection in research outweigh the risk of potential adverse effects only in cases where studies are conducted with symptomatic people actively seeking for support, e.g. as they utilize the services of memory clinics. Conclusion: In the case of non-symptomatic volunteers, the result of the risk-benefit-assessment seems to be less distinctive. Given that disclosing results can, at least initially, cause severe distress and harm and taking into account that research examinations have a significantly increased risk of producing false-positive findings, we suggest to make use of a research-ethical “princple of caution” that supports a restrictive disclosure policy for the second group of potential study participants. This differentiated view on the benefits of disclosed findings in AD research is reflected in recommendations for the set-up of return of result processes.
Keywords: risk benefit assessment